PERFORMANCE EVALUATION OF PARABOLIC CONCENTRATOR WITH THERMAL STORAGE SYSTEM FOR DOMESTIC APPLICATIONS - BANDE A. B.,; GARBA M. M.,; ALIYU S.,; HAMZA B.S.,; SHEHU A., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Solar energy is a free natural resource but its harvesting requires a high capital investment which prohibits its maximum exploitation. A Parabolic Dish Solar Collector (PDSC) with a thermal storage system was been constructed and developed to harness solar beam radiation. The thermal storage system and PDSC were constructed using locally and less cost materials such as galvanized metal sheet and steel rods curved to obey the equation of a parabola then welded together with circular support rings which was then lined with stainless steel reflector pasted for the construction of PDSC. The receiver was made of blackened aluminium material incorporated with coiled copper tube carrying water as the heat transfer fluid. A parabolic dish which acts of a heat collector is used to track and reflects solar radiation at a single point (focus) on a receiver absorber. Heat transfer from the solar collector to the storage tank was done by using thermosyphonic principle to circulate the water (heat transfer fluid) between storage tank and heating system (receiver). The evaluation of thermal storage and analyzing the efficiency of tracking and non-tracking parabolic dish solar collector was carried out during month of June, 2020 for the composite climate of Sokoto. According to the finding, the efficiency of tracking PDSC with thermal storage system and non- tracking PDSC with thermal storage tank were determined and obtained to be 52.9% and 50% respectively.